The Influence of Keel Bone Damage on Welfare of Laying Hens - Riber, Anja B.; Casey-Trott, Teresa M.; Herskin, Mette S. (Frontiers in Veterinary Science, 2018)
This paper reviews current knowledge about welfare implications of keel bone damage in laying hens. As an initial part, we shortly describe the different conditions and present major risk factors as well as findings on the prevalence of the conditions. Keel bone damage is found in all types of commercial production, however with varying prevalence across systems, countries, and age of the hens. In general, the understanding of animal welfare is influenced by value-based ideas about what is important or desirable for animals to have a good life. This review covers different types of welfare indicators, including measures of affective states, basic health, and functioning as well as natural living of the birds, thereby including the typical public welfare concerns. Laying hens with keel bone fractures show marked behavioral differences in highly motivated behavior, such as perching, nest use, and locomotion, indicating reduced mobility and potentially negative affective states. It remains unclear whether keel bone fractures affect hen mortality, but there seem to be relations between the fractures and other clinical indicators of reduced welfare. Evidence of several types showing pain involvement in fractured keel bones has been published, strongly suggesting that fractures are a source of pain, at least for weeks after the occurrence. In addition, negative effects of fractures have been found in egg production. Irrespective of the underlying welfare concern, available scientific evidence showed that keel bone fractures reduce the welfare of layers in modern production systems. Due to the limited research into the welfare implications of keel bone deviation, evidence of the consequences of this condition is not as comprehensive and clear. However, indications have been found that keel bone deviations have a negative impact on the welfare of laying hens. In order to reduce the occurrence of the conditions as well as to examine how the affected birds should be treated, more research into the welfare implications of keel bone damage is needed. Research should focus on effects of genetic lines, genetic selection, housing, and nutrition for the development, prevalence, and severity of these conditions, preferably conducted as longitudinal and/or transnational studies.